PENGETAHUAN KELUARGA TENTANG PENYEBAB PENINGKATAN HIPERKOLESTROLEMIA - Novia Elidayanti Gurning; Joni Siagian (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Families play an important role in preventing the rise of cholesterol levels because adequate understanding of causal factors helps support healthier lifestyle behaviors. This study aims to describe the level of family knowledge regarding the causes of increased cholesterol levels in Mekar Mulio Village, Sei Balai District, Batu Bara Regency. This research used a descriptive survey method involving thirty families who met the study criteria, and data were collected using a structured questionnaire. The findings showed that family knowledge was categorized as low, reflected by limited ability to recognize factors that contribute to elevated cholesterol levels, including high-fat food consumption, insufficient physical activity, stress, smoking habits, and hereditary influences. These results indicate that families require more focused health education to improve understanding and encourage lifestyle changes that support better cholesterol management. The study suggests the implementation of continuous educational programs to strengthen the role of families in preventing increased cholesterol levels through improved dietary habits and healthier daily practices.